Maximizing Firm Value: The Moderating Effect of CSR on Profitability and Capital Structure - Vika Dyah Puspita; Sadeli (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2024)
In addition to analyzing the moderating effect of Corporate Social Responsibility (CSR) Disclosure, the goal of this study is to investigate the link between Profitability, Capital Structure, and Firm Value. The study's emphasis is on coal subsector firms that were listed between 2018 and 2022 on the Indonesia Stock Exchange. The study falls within the realm of explanatory research. The sampling technique uses purposive sampling. The total population in this study was 31 companies. The total sample was 11 companies that met the research criteria. The analysis technique used in this research is Moderated Regression Analysis (MRA) The findings reveal that Profitability significantly impacts Fim Value, whereas Capital Structure does not exhibit a significant effect. Furthermore, the impact of both capital structure and profitability on firm value is considerably mitigated by corporate social responsibility (CSR), particularly when using Debt to Assets Ratio (DAR) indicators. Furthermore, it is evident that taking into account both profitability and capital structure at the same time has a big impact on firm value, further enhanced when moderated by CSR.